2018
DOI: 10.1093/nar/gky177
|View full text |Cite
|
Sign up to set email alerts
|

An origin of the immunogenicity of in vitro transcribed RNA

Abstract: The emergence of RNA-based therapeutics demands robust and economical methods to produce RNA with few byproducts from aberrant activity. While in vitro transcription using the bacteriophage T7 RNA polymerase is one such popular method, its transcripts are known to display an immune-stimulatory activity that is often undesirable and uncontrollable. We here showed that the immune-stimulatory activity of T7 transcript is contributed by its aberrant activity to initiate transcription from a promoter-less DNA end. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
187
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(193 citation statements)
references
References 37 publications
6
187
0
Order By: Relevance
“…We wanted to investigate whether high-temperature IVT affected the formation of antisense-dependent dsRNA structures. Because we were unable to detect the formation of the antisense RNA in any of our templates under native conditions (data not shown), we tested the same sequence that was reported in the previous study (template 512B) (Mu et al 2018). With the 512B template, we were able to detect the formation of RNA molecules that were sensitive to RNase III treatment when transcription was performed with either wild-type RNAP (Fig.…”
Section: A B C Dmentioning
confidence: 77%
See 2 more Smart Citations
“…We wanted to investigate whether high-temperature IVT affected the formation of antisense-dependent dsRNA structures. Because we were unable to detect the formation of the antisense RNA in any of our templates under native conditions (data not shown), we tested the same sequence that was reported in the previous study (template 512B) (Mu et al 2018). With the 512B template, we were able to detect the formation of RNA molecules that were sensitive to RNase III treatment when transcription was performed with either wild-type RNAP (Fig.…”
Section: A B C Dmentioning
confidence: 77%
“…A previous report has demonstrated the synthesis of antisense RNA molecules that can base-pair with the run-off transcript and contribute to the formation of dsRNA contaminants in the IVT reaction (Mu et al 2018). We wanted to investigate whether high-temperature IVT affected the formation of antisense-dependent dsRNA structures.…”
Section: A B C Dmentioning
confidence: 99%
See 1 more Smart Citation
“…A highly purified RNA drug substance is critical for the potency of an mRNA vaccine, because contaminants can activate non-specific or undesirable innate sensors. [34][35][36][37] Karikó et al, 36,38 and more recently Foster et al, 39 have demonstrated that purification of mRNA from double-stranded RNA (dsRNA) contaminants can enhance in vivo translation and reduce innate immune activation, and is critical for the success of RNA-based gene therapy and CAR T cell therapy applications. After purification, mRNA is exchanged into a final storage buffer or formulated with the delivery system for use.…”
Section: Cell-free Production and Purification Of Mrna Vaccinesmentioning
confidence: 99%
“…In vitro transcription with T7 phage RNA polymerase is one of the most common methods for preparing RNAs. But it is known to generate a variety of unintended by-products, one of which is dsRNA formed by intended sense RNA and fully complementary antisense RNA (9). This can lead to misdefining RNA specificity for a protein that is in fact dsRNA specific (10).…”
Section: Introductionmentioning
confidence: 99%